Qualidade do ar em escolas de Curitiba - Avigo Junior, Devanir (2008)
High levels of pollution are associated with respiratory diseases and constitute one of the leading causes of illness for both adults and children. Children are considered potentially more vulnerable to environmental-related health problems than adults, because they are more susceptible to hazardous pollutants. Two schools in Curitiba, Brazil, were selected to characterize the particulate matter indoor and outdoor of the classrooms, in order to access the indoor air quality. Aerosol samples were collected during the regular school year for fine and coarse particles and bulk; they were analysed by electron- probe microanalysis, including facilities for low- Z element determination (low-Z EPMA) and by energy-dispersive X-ray fluorescence (EDXRF), in order to investigate the elemental composition of individual particles and bulk samples, respectively. The concentrations of BTEX, NO2, SO2, O3, HAc and Hfor were assessed using passive diffusion tubes. BTEX were analyzed by gas chromatography–ion trap mass spectrometry (GC-MS) while the remnants gaseous by ion chromatography (IC). The ratio between internal and external concentration of NO2 and SO2 showed different profiles due to the gases analysed and also the different schools. The concentration of NO2 varied between 9,5 and 23,2 µg/m3 , whereas SO2 showed an intermission from 0,1 to 4,8 µg/m3 . Within the schools, BTEX concentrations were predominant. The enrichment factor was calculated showing high contribution of S, Cl, Ca and Zn. The HAc and Hfor inside the classrooms revealed medium concentrations of 1,51 µg/m3 and 1,25 µg/m3 respectively. The chemical compositions of individual particles were quantitatively elucidated, including low-Z components like C, N and O, as well as higher-Z elements, using automated electron probe microanalysis. Samples were further analysed for chemical and morphological aspects, determining the particle size distribution and classifying them according to elemental composition associations. Five classes of particles were identified based on major elemental concentrations: aluminosilicate, soot, organic, calcium carbonate and iron-rich particles. The majority of the respirable particulate matter found inside of the classroom was composed of soot. In view of the chemical composition and size distribution of the aerosol particles, local deposition efficiencies in the human respiratory system were calculated revealing the deposition of soot at alveolar level. The results showed that on average 42 % of coarse particles are deposited at the extrathoracic level while 24% are deposited at the pulmonary region. The fine fraction showed a deposition rate of approximately 18% for both deposition levels.